2015
DOI: 10.1177/0145445515598142
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Acceptance and Commitment Therapy for Depressive Symptoms With Minimal Support

Abstract: Low-intensity interventions for people suffering from depressive symptoms are highly desirable. The aim of the present study was to investigate the outcomes of a web-based acceptance and commitment therapy (ACT)-based intervention without face-to-face contact for people suffering from depressive symptoms. Participants (N = 39) with depressive symptoms were randomly assigned to an Internet-delivered acceptance and commitment therapy (iACT) intervention or a waiting list control condition (WLC). Participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 209 publications
(329 reference statements)
3
78
0
1
Order By: Relevance
“…Therapist guidance was provided in eight of these studies (Buhrman et al, 2013;Hesser et al, 2012;Kristjánsdóttir et al, 2013;Lappalainen et al, 2014;Lappalainen, Langrial, Oinas-Kukkonen, Tolvanen, & Lappalainen, 2015;Pots et al, 2015;Trompetter, Bohlmeijer, Veehof, & Schreurs, 2015;Weineland, Arvidsson, Kakoulidis, & Dahl, 2012), the duration FIGURE 1 Flow diagram of study selection. Note.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapist guidance was provided in eight of these studies (Buhrman et al, 2013;Hesser et al, 2012;Kristjánsdóttir et al, 2013;Lappalainen et al, 2014;Lappalainen, Langrial, Oinas-Kukkonen, Tolvanen, & Lappalainen, 2015;Pots et al, 2015;Trompetter, Bohlmeijer, Veehof, & Schreurs, 2015;Weineland, Arvidsson, Kakoulidis, & Dahl, 2012), the duration FIGURE 1 Flow diagram of study selection. Note.…”
Section: Interventionsmentioning
confidence: 99%
“…Participants rated the treatments as satisfactory (Trompetter et al, 2015;Lappalainen et al, 2014Lappalainen et al, , 2015, enjoyable (Glick & Orsillo, 2015), useful (Kristjánsdóttir et al, 2013), and helpful (Cukrowicz & Joiner, 2007), as measured by the Client Satisfaction Questionnaire (Attkisson & Zwick, 1982), visual analogue scales, and brief questionnaires, respectively. Four studies administered the Credibility/Expectancy Questionnaire (Borkovec & Nau, 1972;Devilly & Borkovec, 2000) and ratings indicated that participants perceived the third-wave eHealth treatments as credible (Kelly & Carter, 2015;Ljótsson et al, 2010;Ly et al, 2014).…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…The app was originally designed as a toolkit of exercises to (1) teach psychological flexibility through the ACT processes and skills and (2) support learning ACT as a daily habit. Similar methods and exercises had previously been studied in treatment of depression symptoms with web-based interventions [27,28,37,38]. The app was available for the Android platform at the time of the study (September 2013).…”
Section: Mobile Appmentioning
confidence: 99%
“…Lappaplainen et al 2015 investigated the effectiveness of an internet based ACT intervention in participants with depression symptoms. Conclusions of the study showed a decrease on depression symptoms which maintained through 12-month follow-up compared to the waitlist group [24].…”
Section: Introductionmentioning
confidence: 79%